Programa Institucional de Bolsa de Iniciação à Docência: contribuições, limites e desafios para a formação docente - Deimling, Natalia Neves Macedo (2014)
This study had as principal focus the identify and analyze of the contributions and limitations of the Programa Institucional de Bolsa de Iniciação à Docência (PIBID) of the Universidade Tecnológica Federal do Paraná (UTFPR) for the training of teaching initiation scholarship fellows and teaching professional practice of supervisors of basic education, employees and institutional, management processes educational and area coordinators program. For both, a qualitative approach research was performed with one institutional coordinator, two area coordinators in managing educational process, four area coordinators, seven supervisors, four employees and forty eight teaching initiation scholarship fellows of four subprojects PIBID UTFPR: subproject Physics, campus Curitiba, subproject English Letters, campus Pato Branco, subproject Mathematics, campus Toledo and subproject Chemistry, campus Londrina. As a tool for data collection, semi-structured interviews, documents and written narratives provided by the participants were used. For data analysis, we considered the theoretical and political affecting that directly or indirectly influence the processes of teacher training aspects; the national policy of teacher education, the legal instruments that based PIBID and the interpretation of the participants about the influences, contributions and limitations to the program for teacher education and action. The data analysis conducted from this perspective allowed us to discuss the relationship between the career choices of teaching initiation scholarship fellows and objective working conditions and career they see and experience in schools in which they are inserted through the Program; the influences - positive and negative - of the activities and actions developed in schools and at the university in the subprojects analyzed - in training and professional practice of teaching involved; the relationship between the university, the partner schools and the state schools and the role and return each of these spheres in the development activities PIBID; and resources and material conditions that are offered to the program to achieve their goals and for the training and teaching professional practice of its participants. Each of these aspects was analyzed separately in four major categories of analysis, from which we discuss broadly and at the same time, particularly the contributions, limitations and challenges of the program for the training and professional practice of its participants. From the results obtained, we believe that the development of policies and programs that aim to facilitate and mediate the contact of students with professional practice of teaching in the period of initial training, as well as the closely relationship between the university and the school, as is the PIBID case, it is essential for both the processes of teaching and practice professional as to the quality of this process. However, thinking about education policy and, more specifically, a politics teacher training involves dealing with the same seriousness, both the processes of initial and ongoing training as the actual working conditions, salary and teaching career - both basic education as higher education - in the search for quality education in real terms and not just formal terms.